Histoplasmosis-Induced Hemophagocytic Lymphohistiocytosis in an Adult Patient: A Case Report and Review of the Literature - Ramona Vesna Untanu; Syed Akbar; Stephen Graziano; Neerja Vajpayee (Case Reports in Infectious Diseases)
Hemophagocytic lymphohistiocytosis (HLH) is an aggressive and life-threating immune dysregulation syndrome characterized by persistent activation of the mononuclear phagocytic system leading to uncontrolled systemic hyperinflammatory response. The proliferation and activation of histiocytes and lymphocytes lead to production of large amounts of cytokines, also called cytokine storm. Hematopoietic and lymphoid tissues are directly involved while other organs are damaged by circulating cytokines. Primary HLH is attributed to genetic defects of the immune system and secondary HLH is usually seen in adults secondary to malignancy, infection, or autoimmune diseases. Zoonotic diseases including fungal infections are an important cause of HLH. Secondary HLH can delay the recognition of the underlying zoonoses. We report the case of a 61-year-old female with history of rheumatoid arthritis with histoplasmosis associated hemophagocytic lymphohistiocytosis.